Magnolia tapichalacaensis (M. sect. Splendentes, Magnoliaceae), a new species from the Andean foothills of Zamora Chinchipe, Ecuador - Pérez, Álvaro J.; Rea, Edison; Martínez, Jennifer; Hidalgo, Fanny; Mendoza, Franco; Mendoza, Ramiro; Díaz, Nelson Jaramillo; Archila, Fredy; Burgess, Kevin S.; Zenil-Ferguson, Rosana; Vázquez-García, J. Antonio (Phytotaxa, 2025)
Magnolia tapichalacaensis is described from the cloud forest remnants of Quebrada Honda, Tapichalaca Reserve in the Zamora Chinchipe Province, south-east Ecuador. This species is characterized by its tomentose leaves and hypsophyll, flowers 5.6–7.5 cm in diameter with three sepals that are abaxially tomentose to villous and adaxially glabrous, petals 9–10, stamens 54–63, gynoecium densely tomentose with 4–5 carpels and densely tomentose ellipsoid fruits. An illustration, photos and a distribution map for the new species are provided. Relationships with other species are discussed, and preliminary conservation status of Critically Endangered (CR) is assigned. Finally, an updated list of Ecuadorian magnolias is presented.